Meaning of health when living in a mining city: a qualitative study in health professionals - Muñoz, Carmen (2020)
Introduction: The chemical substances are highly toxic for intake by metallic smoke. La Oroya is a mining city which comprises a group of foundries and refineries, and catalogued as the fifth most polluted city in the world, bringing about harmful healthy effects. Despite health professionals knows the pollution consequences in health, they continue working. Objective: Identify, analyse and understand the meaning of health by health professionals living in a mining city. Methods: A qualitative study based on the analysis of social representations. A total of 13 health professionals with a minimum of 10 years’ experience. Classified in “foreigner” and “native”. The technique was a semi-structured interview and was applied a questions guide sustained in the universe of beliefs. ATLAS.ti was used as qualitative data analysis software. Results: The category “Health and Wellness” was identified. The sub-categories “Psychosocial” linked to good interpersonal relationships and quite life, and “Physical aspects” divided into healthy practices and health problems; were found too. Conclusions: The health professionals’ definition of health means a new way of live in spite of the pollution of a mining city. Foreigners have more health problems than natives and do not have good physical activity. Both groups create habits, motivated by economic benefits, good relations with patients and co-workers and the vocation of professional service.